Pro-poor Growth during Exceptional Growth. Evidence from a Transition Economy - Paolo Verme (The European Journal of Comparative Economics, 2006)
The paper uses a range of methods to assess changes in income, poverty and income distribution between 2001 and 2002 in Kazakhstan. It is found that outstanding GDP growth has been translated into very modest growth in mean household income. However, both income poverty and inequality have decreased significantly and growth has been 'pro-poor', which is explained by changes in inequality accounting for almost all the changes in poverty. The elasticity of poverty with respect to both growth and inequality is also found to be high. These findings suggest that GDP changes can be, at times, disjoint from household income performance and that, when this happens, income redistribution can still play a key role for poverty reduction. Yet a much greater reduction in poverty would have occurred if mean income would also have risen. Hence, the distribution of GDP growth among factors of production and the distribution of income among households are the cornerstones of poverty reduction rather than GDP growth alone.